The Gambia : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper examines economic developments in The Gambia during 1994-98. Although real output growth slowed significantly in the early 1990s and turned negative in 1994/95, both 1997 and 1998 were characterized by an upswing in real economic activity. The 1994/95 output decline of 3.4 percent was primarily owing to a significant downturn in tourist activity. The recovery in the tourist sector and the more favorable weather conditions led to real GDP growth of 4.9 percent in 1997 and an estimated real growth rate of 4.7 percent in 1998.